FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN BBLR (BAYI BERAT LAHIR RENDAH) DI RSU Dr. WAHIDIN SUDIRO HUSODO MOJOKERTO - Purwati, Heni; Maharani, Kartika (JURNAL KEPERAWATAN SEHAT, 2016)
Babies with low birth weight is one of the main causes of infant mortality in the world. Impact low birth weight baby greater than in normal infants at the same gestational age. This study aims to determine the factors that affect mothers low birth weight babywith descriptively based on age, parity, education level, job, Haemoglobin Estimated and Disease/complications. This study used a non Random Sampling (Non probality) type of purposive sampling. The population was all mothers who gave birth to low birth weight mothers gained 97 and obtained samples of 44 mothers. Data taken from medical records, inserted into the data tabulation table. After collected entered data processing andincluded in the frequency distribution table. The final conclusion is low birth weight baby found in the age group 20-35 years by 25 mothers (56.8%). Multipara maternal parity on as many as 23 mothers (52.3%). Mother’s education level at the high school by 20 mothers (45.5%). Mother’sjob as a Housewife of 37 mothers (84.1%). Mother’s have Haemoglobin Estimate ≥11gr/dL by 26 mothers (59,1%).Mothers don’t have complications there were 28 mothers (63.6%). In this study found no dominant factors affecting the incidence of low birth weight baby. To decrease the incidence of low birth weight babies by providing information about nutrition during pregnancy because it is so related to the health of the fetus.Keywords:Age, Parity, Education Level, Job, Haemoglobin Estimated,Diseases/Complications, Low Birth Weight Babies